Government Policy on the Management of Competency Development for Indonesian Air Force Avionics Technicians to Support National Defense Self Reliance (Case Study: Maintenance Unit 21, Depohar 20) - Melta, Mochamad; Yunanto, Sri; Hasanudin, Usni (International Journal of Social Service and Research, 2026)
This research aims to analyze government policy in the management of the development of the competence of Indonesian Air Force avionics technicians to support national defense independence, with a case study in Maintenance Unit 21 Depohar 20. The study uses a qualitative approach with descriptive-analytical methods through interview techniques, observation, and document study. The results of the study indicate that the policy of developing the competence of avionics technicians has not been fully able to meet the needs of the quantity and quality of human resources. There is a significant gap between the needs and the realization of the number of technicians, as well as limited competence that is still dominated by internal certification and does not meet global standards. From a managerial aspect, the implementation of the POAC function has not been running optimally, especially in the planning, implementation, and supervision stages. In addition, collaboration between the government, the Indonesian Air Force, the defense industry, and universities within the Triple Helix framework has not been effectively integrated, thus hampering technology transfer and competency improvement. The gap between policy and implementation indicates that the policy is still normative and not fully operational. This study concludes that an integrative, adaptive, and collaborative policy model is needed to improve the competence of avionics technicians in a sustainable manner to support national defense independence.